STRATEGI DAN KONSEP PENGENDALIAN INTERNAL PADA OT GROUP - Lukman Surjadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Tarumanagara, 2023)
The purpose of this study is to analyze how from a problem can analyze from the control carried out by theOT Group. In this topic, will discuss about the factors that can af ect internal control itself, its objectives,components, to